Tracing the history of the development and management of two irrigation systems in the terai of Nepal - Prasad, Krishna C., author; Thoreson, Bryan P., author; Molden, David J., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2000)
Significant effort has been placed on increasing irrigated area, agricultural performance and improving overall irrigation system performance. Sometimes, these efforts are successful, but often frustrations are met. A wide variety of experiences have been gained, but unfortunately many of these experiences are not well documented. These are lost learning opportunities. The purpose of this paper is to trace the history of two irrigation systems in Nepal to help fill this gap in recording experiences. The two study systems are the Khageri system serving about 3,900 ha and the West Gandak system serving about 10,300 ha. Both systems are located in the terai, the plains of Nepal, and were originally constructed in the 1960s and 70s. They are run-of-the-river systems, originally designed to provide supplemental water to paddy during the monsoons. Main and secondary canal systems were provided for both, and farmers were expected to construct the tertiary system. Both systems have undergone significant modernization of infrastructure and institutions to provide better flow control for paddy irrigation and, at West Gandak, for winter crops. Recent efforts have been to increase the involvement of farmers in managing the irrigation system through a management transfer program. While partial success has been achieved, sustainability remains uncertain. This presentation tracks the development history of the systems, showing significant changes and their consequences on performance. We demonstrate that a balance between institution and infrastructure development must be achieved for success. We show the need for effective institutions to support local managing agencies. Future development paths are suggested. The experiences of these two systems, while in many ways unique, are also in many ways typical of irrigation development.
Irrigation and drainage in the new millennium
Not digitized by CSUL Digital Services.
Presented at the 2000 USCID international conference, Challenges facing irrigation and drainage in the new millennium on June 20-24 in Fort Collins, Colorado.